Clinical judgment and diagnostic reasoning of nursing students in clinical simulation - Janaina Gomes Perbone Nunes; José Joaquim Penedos Amendoeira; Diná de Almeida Lopes Monteiro da Cruz; Kathie Lasater; Sheila Coelho Ramalho Vasconcelos Morais; Emilia Campos de Carvalho
ABSTRACT Objectives: to determine the degree of association between clinical judgment and diagnostic reasoning of nursing students in clinical simulation. Methods: this is a correlational research design using a quantitative approach. The sample consisted of 41 nursing students who assisted a patient with vaso-occlusive crisis in a high-fidelity clinical simulation setting. The instruments used included the Lasater Clinical Judgment Rubric - Brazilian Version and the Diagnostic Thinking Inventory. Results: clinical judgment was associated with diagnostic reasoning (r=0.313; p=0.046), as well as the "noticing" aspect of clinical judgment with diagnostic reasoning (r=0.312; p=0.047). Conclusions: the results show that skills to interpret patient data are associated with diagnostic reasoning skills. Teaching clinical judgment skills is necessary to develop the diagnostic reasoning of nursing students.